Occupied Territory : Policing Black Chicago from Red Summer to Black Power - Balto, Simon (Justice, power, and politics., 2019)
In July 1919, an explosive race riot forever changed Chicago. For years, black southerners had been leaving the South as part of the Great Migration. Their arrival in Chicago drew the ire and scorn of many local whites, including members of the city's political leadership and police department, who generally sympathized with white Chicagoans and viewed black migrants as a problem population. During Chicago's Red Summer riot, patterns of extraordinary brutality, negligence, and discriminatory policing emerged to shocking effect. Those patterns shifted in subsequent decades, but the overall realities of a racially discriminatory police system persisted. In this history of Chicago from 1919 to the rise and fall of Black Power in the 1960s and 1970s, Simon Balto narrates the evolution of racially repressive policing in black neighborhoods as well as how black citizen-activists challenged that repression. Balto demonstrates that punitive practices by and inadequate protection from the police were central to black Chicagoans' lives long before the late-century "wars" on crime and drugs. By exploring the deeper origins of this toxic system, Balto reveals how modern mass incarceration, built upon racialized police practices, emerged as a fully formed machine of profoundly antiblack subjugation.